2019
DOI: 10.1182/blood-2019-128717
|View full text |Cite
|
Sign up to set email alerts
|

S100A9 Contributes to T Cell Dysfunction through Its Interaction with RAGE in MDS

Abstract: We have previously reported that the overexpression of S100A9 drives the development of Myelodysplastic Syndrome (MDS) through expansion of Myeloid Derived Suppressor Cells (MDSC) and promotion of pyroptosis. Despite the identified role of S100A9's effects on MDSC, and hematopoietic stem and progenitor cells (HSPC), as well as their establishment of an immunosuppressive microenvironment, the effects of S100A9 on adaptive immunity in MDS progression are less clear. Here, we report for the first time the unident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…6E and F. Notably, proliferation inhibitory genes S100A9, S100A8 [51], and Cebpb , together with T N ‐associated genes, such as Ccr7 , Pecam1 , Ptk2 , Icos , Cd27 , were significantly downregulated in T SCM CD122 hi . Whereas genes associated with activation and memory T‐cell phenotype, such as Ccr6 , Cxcr6 , Il12rb2 , Il18rap , were upregulated in the T SCM CD122 hi subset (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6E and F. Notably, proliferation inhibitory genes S100A9, S100A8 [51], and Cebpb , together with T N ‐associated genes, such as Ccr7 , Pecam1 , Ptk2 , Icos , Cd27 , were significantly downregulated in T SCM CD122 hi . Whereas genes associated with activation and memory T‐cell phenotype, such as Ccr6 , Cxcr6 , Il12rb2 , Il18rap , were upregulated in the T SCM CD122 hi subset (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptomic differences were observed when comparing the T SCM CD122 hi/lo and T SCM CXCR3 hi/lo subsets. The T SCM CD122 hi subset demonstrated significant downregulation of proliferation inhibitory genes, S100A9 and S100A8, which have previously been reported to be responsible for decreased proliferative responses of T cells [51]. Previous studies have shown that the expression level of the components of the IL‐12 receptor ( Il12rb2 ) and IL‐18 receptor ( Il18rap ) increase in a stepwise manner among memory CD8 T cells in association with increasing antigen encounter times [63].…”
Section: Discussionmentioning
confidence: 99%